The Influence of HR Service Quality and Organizational Support on Organizational Commitment Through Job Satisfaction as an Intervening Variable - Nurul Intan Sari; Hernawaty; Husni Muharram Ritonga (International Journal of Management, Economic and Accounting, 2026)
This study examines the extent to which HR service quality and perceived organizational support shape employee commitment, positioning job satisfaction as a mediating mechanism among female employees of PT Permodalan Nasional Madani (PNM) Medan Branch. A quantitative-explanatory survey design was adopted. Fifty female employees working outside the HR department were recruited via purposive sampling, in line with the PLS-SEM minimum sample guideline of ten times the maximum number of paths entering any endogen construct (Hair et al., 2021). A five-point Likert-scale questionnaire served as the data collection instrument, and analysis was conducted through PLS-SEM using SmartPLS 4.0. Key findings indicate that: (1) HR service quality exerts a positive and significant effect on both job satisfaction (β = 0.412; p < 0.05) and organizational commitment (β = 0.287; p < 0.05); (2) organizational support likewise positively influences job satisfaction (β = 0.389; p < 0.05) and organizational commitment (β = 0.341; p < 0.05); (3) job satisfaction is a significant predictor of organizational commitment (β = 0.463; p < 0.05); and (4) job satisfaction serves as a partial mediator between both independent variables and organizational commitment.